Pilot-scale CO2 Sequestration Test Site in the Sulcis Basin (SW Sardinia): Preliminary Site Characterization and Research Program. (July 2017) - Plaisant, Alberto; Maiu, Arianna; Maggio, Enrico; Pettinau, Alberto
Abstract: The deep aquifer located at a depth of about 1000-1500 m within fractured carbonate in the Sulcis coal basin (South-West Sardinia, Italy) constitutes a potential reservoir to develop a pilot-scale CO2 storage site. The site is well known in terms of stratigraphy and structural settings, due to the data available from the coal mining activity. On the basis of these data, a potential deep reservoir and the caprock can be recognized; more in detail, in the southern sector of the basin, the top of the potential reservoir reaches a suitable depth for storage. At the same time, the already existing infrastructures (the Sotacarbo Research Centre on carbon capture, utilization and storage), coupled with some peculiar features (as the low natural seismicity, the hydrogeological system, etc.) makes the Sulcis area a potential experimental site capable to further develop CO2 storage technologies, such as low-cost drilling, site monitoring, and experimental studies on CO2 diffusion and leakage. In this context, Sotacarbo (in cooperation with ENEA, the Universities of Cagliari and Rome "La Sapienza", OGS, INGV and RSE) is leading a very ambitious research program, funded by both the Italian and the Sardinian Regional Governments within two different and complementary projects, to characterize the Sulcis coal basin as a potential site for the development of CO2 geological storage technologies. The research activities are structured in two different phases: (i) site characterization, including the construction of an underground and a fault laboratories and (ii) the installation of a test site for small-scale injection of CO2 . In particular, the underground laboratory will host geochemical and geophysical experiments on rocks, taking advantages of the buried environment and the very well confined conditions in the galleries; in parallel, the fault laboratory will be constructed to study CO2 leakage phenomena in a selected fault. Overall, the project, which is currently ongoing, will allow to characterize the Sulcis basin and to develop a permanent infrastructure (know-how, equipment, laboratories, etc.) for advanced international studies on CO2 storage. This work describes the whole Sulcis CO2 storage project, highlighting its current status, some of the preliminary results of site characterization phase, planned activities and the links with the research activities on carbon capture and utilization.